Pathogenesis of Psoriasis: The Role of Pro-Inflammatory Cytokines Produced by Keratinocytes - Balato, Anna; Balato, Nicola; Megna, Matteo; Schiattarella, Maria; Lembo, Serena; Ayala, Fabio (IntechOpen, 2012)
None